Variability and Intensity of the Sea Surface Temperature Front Associated With the Kuroshio Extension - Xi, Jingyuan; Wang, Yuntao; Feng, Zhixuan; Liu, Yang; Guo, Xinyu (Frontiers in Marine Science, 2022)
Seventeen years of satellite observational data are used to describe the variability in sea surface temperature (SST) fronts and associated features, e.g., frontal intensity and probability, in the northwestern Pacific Ocean. Compared with the SST gradient and frontal probability, the frontal intensity is less impacted by background noise in satellite observations and precisely represents the variability in frontal patterns. The seasonal variability in frontal intensity is prominent, and the corresponding seasonality varies spatially. Fronts are more common during winter in the northern region around the Oyashio Current but are most common during spring in the Kuroshio Current and to the south of the Kuroshio Extension. The meridional migration of fronts is associated with the seasonal movement of the North Pacific subtropical gyre. Though overall averaged frontal intensity along the Kuroshio Extension is most prominent in the northwestern Pacific Ocean, the associated variability in fronts is highly complex. The current study reveals that seasonality itself cannot capture the whole picture of frontal features because eddy-induced intraseasonal variability and basin-scale signal-induced interannual variability can modulate frontal dynamics. In particular, the monthly frontal intensity in regions where the seasonal cycle is not significant depends on the Pacific Decadal Oscillation and North Pacific Gyre Oscillation. Furthermore, the oscillation of the Kuroshio Extension and associated mesoscale eddies can impact its intraseasonal variability. The comprehensive analysis of frontal intensity in the Kuroshio Extension is helpful for delineating regional dynamics and has the potential to improve our understanding of controls on marine primary production.